Adjuvant Treatment with Empagliflozin or Semaglutide Increases Endothelial Progenitor Cells in Subjects with Well-Controlled Type 1 Diabetes Mellitus - Maja Preložnik Navodnik; Katarina Reberšek; Katarina Klinar; Andrej Janež; Helena Podgornik (Current Issues in Molecular Biology)
Circulating endothelial cells (CECs) and endothelial progenitor cells (EPCs) are promising markers of vascular damage and endothelial regeneration potential. We focused on the detection of CECs and EPCs using flow cytometry with regard to analytical challenges and its suitability for routine testing. As part of a clinical validation, CECs and EPCs were measured in blood samples from 83 subjects with type 1 diabetes (T1DM), evaluating an adjuvant intervention with two different antidiabetic drugs, empagliflozin (N = 28) and semaglutide (N = 29). Both groups receiving adjuvant therapy were compared with the insulin-only group (N = 26) at two time points: before the start of therapy and after 12 weeks of adjuvant therapy. All three groups were comparable regarding demographic characteristics and concomitant risk factors. Absolute and relative endothelial cell count at baseline were low and comparable to those of healthy individuals. In the group receiving empagliflozin or semaglutide, a significant increase in EPC was observed after 12 weeks of treatment. We demonstrated that EPCs have the potential to serve as markers for monitoring the efficacy of adjuvant therapy in T1DM patients. However, before their implementation in clinical practice, the flow cytometry protocol for CEC and EPC identification and quantification must be standardized.